Infective endocarditis in children: a 23-year experience at a Southern African tertiary institution - Ooka, Meera Chandrakant Natho (My University, 2018)
Background: There is a paucity of data regarding infective endocarditis (IE) in children particularly in low-to-middle income settings with no recent data from Sub-Saharan Africa. Objectives: To determine the demographic and clinical profiles of paediatric patients diagnosed with IE at the Chris Hani Baragwanath Academic Hospital (CHBAH), Johannesburg, South Africa. Methods: A retrospective descriptive study of all paediatric patients diagnosed with IE between 1993 and 2015 and captured on the Paediatric cardiology electronic database. Demographic data, the presence of congenital or acquired structural heart disease and other risk factors, blood culture results and complications were recorded and analysed using basic statistical methods. Results: A total of 183 patients were included in the study. The median age was 31.2 months with a male: female ratio of 1.1:1. Ninety-seven patients (53%) had underlying congenital heart disease (CHD), 26 had rheumatic heart disease (14.2%), and 45 (24%) were identified with structurally normal hearts. Underlying sepsis (37.8%), central venous catheters (31.2%), prematurity (15.6%) and HIV (13.3%) were found to be risk factors in the group with normal hearts. Staphylococcus Aureus and Streptococcus Viridans were found to be the most common offending pathogens. Complications were documented in 103 (56.3%) patients. These included cardiac failure, worsening valve lesions, vascular complications (embolization and mycotic aneurysm formation), other manifestations of sepsis, surgery required to treat complications and death. The overall mortality rate was 23.5%. Cardiac failure and vascular complications were associated with a high risk of mortality. Conclusion: CHD is the most common association with IE followed by structurally normal hearts in premature infants and patients with central venous catheters. More than half the patients suffered complications and almost a quarter died highlighting the devastating outcomes that IE poses
A Research Report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in Paediatrics
Keywords: Endocarditis, Bacterial; Heart defects, Congenital; Heart Diseases--therapy